Simultaneous valve-in-valve procedure and life-saving coronary angioplasty in a patient with low coronary artery ostia - Walczewski, Michał; Gąsecka, Aleksandra; Pęczek, Piotr; Marchel, Michał; Rymuza, Bartosz; Kochman, Janusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 75-year-old woman with hypertension, diabetes mellitus type 2, permanent atrial fibrillation, and chronic kidney disease was admitted to the hospital due to exacerbation of chronic heart failure, vertigo, and syncopal events. Transoesophageal and transthoracic echocardiography revealed severe stenosis and calcification of the prosthetic aortic valve (Trifecta 21 mm), mid-range left ventricle ejection fraction (LVEF) of 49%, moderate insufficiency of the mitral valve, and tricuspid insufficiency with a high probability of pulmonary hypertension. Regarding multiple comorbidities and a high peri-operative risk (logistic EuroScore 48.6%), valve-in-valve (ViV) transcatheter aortic valve implantation (TAVI) was proposed by the heart team.